Forms of the elephant: A pendulous and sinuous trunk—A study of images of the elephant from the perspective of Sino-foreign exchanges in the Han dynasty. Issue 3 (3rd July 2018) - Hu, Zhu
Abstract: Images of the elephant in Han dynasty art serve as an element of the world of mysticism and propitious omens in Han pictorial carvings. Carved stone reliefs on the subject of the elephant dating back to the Han dynasty have been discovered in Shandong, Xuzhou, Henan, Shaanxi, and other regions, frequently appearing in the company of camels and mahouts. The mahouts are intermingled with foreigners in pointed hats and tonsured monks, forming a visual pattern of "foreigners—elephants, " which could be regarded as a product of Sino-foreign exchanges in the Han dynasty. This new style of image was propagated by foreigners residing in China and gradually introduced into the Central Plains via the Silk Road and Buddhism, fusing with images of the elephant in traditional Chinese animal designs dating to the Shang and Zhou dynasties to produce the "six-tusked white elephant, " "monk (immortal) riding an elephant, " and other new content, while also reflecting the interwoven characteristics of early Buddhist and Daoist art.